Growth Mindset Intervention and Academic Achievement: Examining Effects on Underachieving Secondary School Students with Gender Considerations (Journal of Guidance and Counselling Studies, 2025)
This study examines the impact of a structured growth mindset intervention on the academic achievement of underachieving secondary school students in Anambra State. A quasi-experimental pretest-posttest control group design was used, involving 70 academically underachieving secondary school students who were assigned to either an experimental group (N = 37) or a control group (N = 33). The experimental group participated in a 13-week growth mindset intervention, incorporating sessions on neuroplasticity, effort-based learning, and academic resilience, while the control group received no intervention programme. Academic achievement was measured using teacher-made test scores, and ANCOVA was used to test the hypotheses. The experimental group (M = 71.76, SD = 9.78) demonstrated significantly higher post-test academic achievement than the control group (M = 58.50, SD = 10.08), F(1, 65) = 1206.71, p < .001, partial η² = .949, indicating a substantial intervention effect. Additionally, a significant gender difference was found, with female students achieving higher post-test scores than their male counterparts. The intervention was effective across all students, reinforcing the role of growth mindset programmes in enhancing academic outcomes. It was concluded that growth mindset interventions can significantly improve the academic performance of underachieving students, offering a practical, evidence-based strategy for addressing academic challenges.
Keywords: Growth mindset; academic achievement; underachievement; intervention; secondary education; Nigeria